Autocratic, Democratic, Transformational and Charismatic Leadership Styles and Contingency of Different Performance Outcomes in SMEs - Dr. Zafar Iqbal; Dr. Amna Niazi; Dr. Hamid Hassan (Journal of Business & Tourism, 2021)
We analyze four different leadership styles from multiple dimensions to find out the suitability of these styles for the leaders working in Pakistani small and medium enterprises (SMEs). Theoretically, it is an additional perspective in the debate on effectiveness of different leadership styles in different environments for different purposes. It starts with analyzing contemporary theories of leadership and their derivative styles. Next, it discusses the major aspects of organizational environment coming from the broader culture of a country. Subsequently, it tries to provide a more balanced view in the debate on cause and effect of leadership styles and their effectiveness in specific organizational culture. In the empirical analyses the study analyzes the productivity, acceptance and sustainable success of different leadership styles in the organizations working in Pakistan. The data is collected both from business leaders and their relevant followers. The findings of study explains that outputs when measured in terms quantity shows better results for autocratic leadership style while democratic leadership style give better results when measured in terms of quality. Similarly, willingness of followers to continue and their inspirations beyond the formal organizational structure are higher for charismatic and participative leadership styles.